Field Measurement and Energy Analysis of Ground-Borne Vibration around High-Speed Railway Viaduct - Cao, Yanmei; Xiang, Qi; Li, Boyang; Li, Zhaoyang (Shock and Vibration, 2023)
In order to investigate the vibration characteristics and propagation mechanism of ground vibrations induced by high-speed train passing through the viaduct, a field experiment is carried out, and the measured data is deeply analyzed. Besides the independent time domain and frequency domain analysis, the continuous wavelet transform (CWT) is performed on the vibration signal to analyze the energy distribution characteristics of ground vibrations from the view of time-frequency synchronous analysis. The experimental results show that the ground vibrations have obvious nonstationary characteristics; the first dominant frequency of ground vibration is concentrated between 40–55 Hz, which is affected by the excitation frequency of the train wheel axle and the peak frequency of wheel-rail interaction force. The ground vibrations attenuate gradually as the distance from the railway track increases, in which the high-frequency components above 50 Hz attenuate faster, low-frequency components below 8 Hz continuously decay in the near field, and medium-frequency components within 8−50 Hz decay slower with a longer transmission distance. Compared with traditional methods, time-frequency synchronous analysis of ground vibration signals is more accurate and intuitive, and the CWT can be used as a promising method in the analysis of ground-borne vibration from high-speed railway.